Set and Setting in the Santo Daime - Ido Hartogsohn (Frontiers Media S.A., 2021)
Set and setting is a fundamental concept in the field of psychedelic drug research, which points to the profound dependence of psychedelic effects on psychological, social, and cultural factors. Santo Daime is a Brazilian religion that makes elaborate use of ordering principles, techniques, and symbology to shape and direct the effects of the hallucinogenic brew ayahuasca. This paper systematically explores the tapestry of, inter alia, symbolic, social, cultural, psychological, aesthetic and musical elements that participate in the shaping of the psychedelic experience in the context of the Santo Daime ayahuasca religion. The methodically rich under the hood description of the mechanics of entheogenic initiation within the Santo Daime tradition provides a template for future studies of the role of context in psychedelic experimentation.